2018
DOI: 10.1111/jcpp.12911
|View full text |Cite
|
Sign up to set email alerts
|

Investigating late‐onset ADHD: a population cohort investigation

Abstract: BackgroundAdult ADHD has been assumed to be a continuation of childhood‐onset ADHD. However, recent studies have identified individuals with ADHD in adulthood who have not had ADHD in childhood. Whether or not these individuals have a ‘typical’ neurodevelopmental profile is not clear.MethodsWe tested two explanations for the emergence of apparent late‐onset ADHD symptomatology using the ALSPAC epidemiological cohort, by grouping individuals according to their scores on the Strengths and Difficulties Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 34 publications
6
41
0
1
Order By: Relevance
“…In 2015, Moffit and collaborators published a pioneering study demonstrating that nearly 90% of adult ADHD cases in the Dunedin cohort were de novo cases (Moffitt et al., ). Investigators replicated the findings on the existence of late‐onset ADHD in three other large cohort samples: E‐Risk (Agnew‐Blais et al., ), Pelotas Birth Cohort (Caye et al., ) and ALSPAC (Cooper et al., ; Riglin et al., ). These findings raised a debate on whether adult ADHD could be considered a childhood‐onset neurodevelopmental disorder, questioning whether late‐onset ADHD might represent a distinct disorder from childhood‐onset ADHD (Castellanos, ; Moffitt et al., ).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In 2015, Moffit and collaborators published a pioneering study demonstrating that nearly 90% of adult ADHD cases in the Dunedin cohort were de novo cases (Moffitt et al., ). Investigators replicated the findings on the existence of late‐onset ADHD in three other large cohort samples: E‐Risk (Agnew‐Blais et al., ), Pelotas Birth Cohort (Caye et al., ) and ALSPAC (Cooper et al., ; Riglin et al., ). These findings raised a debate on whether adult ADHD could be considered a childhood‐onset neurodevelopmental disorder, questioning whether late‐onset ADHD might represent a distinct disorder from childhood‐onset ADHD (Castellanos, ; Moffitt et al., ).…”
Section: Introductionmentioning
confidence: 73%
“…The first ALSPAC study (Riglin et al., ), which assesses adolescents, did not primarily aim to investigate a specific adolescent‐onset trajectory of ADHD. However, more recently, the ALSPAC data were re‐analyzed in order to specifically investigate an ADHD onset in adolescence (Cooper et al., ). This study showed that there is a distinct group of adolescent‐onset cases, despite the fact that a large proportion of these potential youth‐onset cases were actually misclassified on the basis of their earlier hyperactivity scores on the Strengths and Difficulties Questionnaire (SDQ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in adult ADHD has recently increased, 1 and cases of late-onset ADHD in adulthood in individuals without a history of childhood ADHD have recently been reported. 2 Furthermore, there has been recent controversy surrounding the diagnosis of ADHD in children and adults. 3 The primary symptoms of ADHD differ according to ADHD subtypes, and its progress varies, which have resulted in disagreements over the diagnosis of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Moffitt et al [64] and Agnew-Blais et al [65] observed the Dunedin birth cohort and England and Wales twin birth cohorts, respectively, and reported late-onset ADHD without any childhood history. Cooper et al [66] also reported adult onset ADHD with normal childhood development from a UK birth cohort, which ignited the possibility of a previously unidentified form of ADHD that arises entirely during adulthood. However, there are some caveats to these studies, such as the possibility of biased retrospective recall by the parents for the four-decadelong longitudinal cohort study conducted in Dunedin, New Zealand [64].…”
Section: Late-diagnosed Vs Late-identified Vs Late-onset Adhdmentioning
confidence: 99%